Investigation of the mechanism of tanshinone IIA to improve cognitive function via synaptic plasticity in epileptic rats. (31st December 2023) - Jia, Chen; Zhang, Rui; Wei, Liming; Xie, Jiao; Zhou, Suqin; Yin, Wen; Hua, Xi; Xiao, Nan; Ma, Meile; Jiao, Haisheng
Abstract: Context: Tanshinone IIA is an extract of Salvia miltiorrhiza Bunge (Labiatae) used to treat cardiovascular disorders. It shows potential anticonvulsant and cognition-protective properties. Objective: We investigated the mechanism of tanshinone IIA on antiepileptic and cognition-protective effects in the model of epileptic rats. Materials and methods: Lithium chloride (LiCl)-pilocarpine-induced epileptic Wistar rats were randomly assigned to the following groups ( n  = 12): control (blank), model, sodium valproate (VPA, 189 mg/kg/d, positive control), tanshinone IIA low dose (TS IIA-L, 10 mg/kg/d), medium dose (TS IIA-M, 20 mg/kg/d) and high dose (TS IIA-H, 30 mg/kg/d). Then, epileptic behavioural observations, Morris water maze test, Timm staining, transmission electron microscopy, immunofluorescence staining, western blotting and RT-qPCR were measured. Results: Compared with the model group, tanshinone IIA reduced the frequency and severity of seizures, improved cognitive impairment, and inhibited hippocampal mossy fibre sprouting score (TS IIA-M 1.50 ± 0.22, TS IIA-H 1.17 ± 0.31 vs. model 2.83 ± 0.31), as well as improved the ultrastructural disorder. Tanshinone IIA increased levels of synapse-associated proteins synaptophysin (SYN) and postsynaptic dense substance 95 (PSD-95) (SYN: TS IIA 28.82 ± 2.51, 33.18 ± 2.89, 37.29 ± 1.69 vs. model 20.23 ± 3.96; PSD-95: TS IIA 23.10 ± 0.91, 26.82 ± 1.41, 27.00 ± 0.80 vs. model 18.28 ± 1.01). Discussion and conclusions: Tanshinone IIA shows antiepileptic and cognitive function-improving effects, primarily via regulating synaptic plasticity. This research generates a theoretical foundation for future research on potential clinical applications for tanshinone IIA.